2019
DOI: 10.1042/bsr20190283
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA HOXA-AS2 promotes non-small cell lung cancer progression by regulating miR-520a-3p

Abstract: Background: The HOXA cluster antisense RNA 2 (HOXA-AS2) has recently been discovered to be involved in carcinogenesis in multiple cancers. However, the role and underlying mechanism of HOXA-AS2 in non-small cell lung cancer (NSCLC) yet need to be unraveled. Methods: HOXA-AS2 expression in NSCLC tissues and cell lines was detected using quantitative real-time PCR (qRT-PCR). Furthermore, the effects of HOXA-AS2 on NSCLC cell proliferation, apoptosis, migration, and invasion were assessed by MTS, flow cytometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
(28 reference statements)
2
33
0
Order By: Relevance
“…For instance, in one study, HOXA-AS2 stimulated the proliferation, migration and invasion of osteosarcoma cells [11]. Several studies described HOXA-AS2 as an oncogene that promoted the malignant proliferation of non-small cell lung cancer cells [33][34][35]. Similarly, HOXA-AS2 was demonstrated in another research to advance bladder cancer cells by directly regulating the expression of miR-125b [36].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in one study, HOXA-AS2 stimulated the proliferation, migration and invasion of osteosarcoma cells [11]. Several studies described HOXA-AS2 as an oncogene that promoted the malignant proliferation of non-small cell lung cancer cells [33][34][35]. Similarly, HOXA-AS2 was demonstrated in another research to advance bladder cancer cells by directly regulating the expression of miR-125b [36].…”
Section: Discussionmentioning
confidence: 99%
“…In the end, 12 articles with a total of 796 patients (Table 1) were included in this study. There were 8 types of cancer in these 12 literatures, including 2 cases of lung cancer [17,18], 2 of thyroid cancer [19,20], 1 of bladder cancer [21], 1 of breast cancer [22], 1 of gastric cancer [23], 2 of colorectal cancer [9,10], 1 of osteosarcoma [24] and 2 cases of liver cancer [14,25]. All the 12 articles come from China (Table 1).…”
Section: Incorporate the Results Of The Studymentioning
confidence: 99%
“…At present, studies have confirmed that long-chain non-coding RNAHOXA-AS2 can take part in the progression of AML, thyroid papillary carcinoma, HCC and breast cancer throuh target regulating of miR-520c-3p [12,14,19,22]. In addition, HOXA-AS2 can promote the malignant progression of non-small cell lung cancer, thyroid papillary carcinoma and liver cancer through miRNA-216a-5p, miR-520a-3p, miR-15a-5p and miR-125b [17,18,20,21]. And the KEGG showed that HOXA-AS2 was associated with cancer, MAPK pathway, NOD receptor pathway and Ca ion signaling pathway.…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 99%
“…For instance, HOXA-AS2 has been shown to stimulate osteosarcoma cell proliferation, migration and invasion [11]. Several studies described HOXA-AS2 as an oncogene that promoted the malignant proliferation of non-small cell lung cancer cells [24][25][26]. Similarly, HOXA-AS2 was indicated to advance bladder cancer by directly regulating the expression of miR-125b, thereby regulating Smad2 [27].…”
Section: Discussionmentioning
confidence: 99%